Evaluasi Sistem Informasi Nasmoco Integrated System (NIS) dalam Penjualan Jasa Servis Menggunakan Model HOT-Fit di PT Nasmoco Pekalongan - Geneiro Kaivia Sachi; Prastuti Sulistyorini; Risqiati Risqiati (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
Advances in information technology encourage companies to optimize information systems to support business processes, including automotive service sales. PT Nasmoco Pekalongan uses the Nasmoco Integrated System (NIS) as its primary system for managing service sales activities; however, several issues remain, such as delays in data access, input errors, and suboptimal system integration. This research aims to assess the implementation of NIS through the Human Organization Technology Fit (HOT-Fit) framework, which encompasses the human, organization, and technology dimensions. A descriptive qualitative research method was employed, with data collected through observations, interviews, questionnaires, and documentation review. The results indicate that NIS has been operating well and effectively supports the company’s operational processes. Nevertheless, several aspects still require improvement, particularly user satisfaction, training, coordination, and system reliability. Based on the evaluation results, the implementation of NIS fulfills the human, organization, and technology aspects, thereby supporting the effectiveness of service sales processes at PT Nasmoco Pekalongan.